The Adaptation of the Mestizo Ayacuchano Wayno to the Piano. A Version by the Autodidact Pianist Oswaldo Mendieta Irrazabal - Canelo Marcet, Flor de María Martina (2017)
This paper deals with piano adaptations of Andean folk music, specifically, the mestizo ayacuchano wayno. The wayno is the most popular genre throughout Peru, it is music, poetry and partner dance. This paper analyzes the context in which adaptations of this kind are created on the piano, an instrument assimilated to Andean music in the late nineteenth century; the specific characteristics of the musical elements in the ayacuchano style; and how Oswaldo Mendieta Irrazaval adapts these elements to the piano while adding his personal creativity.